Outpatient psychiatric service utilization during the Covid-19 pandemic - Fateme Shirzad; Mohsen Shati; Seyede Salehe Mortazavi; Shakiba Gholamzad; Shahrzad Ahmadkaraji; Mahdie Pazhooyan; Narges Saeedi; Rana Hashemi; Saeedeh Shirdel; Mahdieh Salehi (Middle East Current Psychiatry, 2022)
Abstract Background The conditions related to the Covid-19 pandemic and quarantine have endangered the mental health of people in the community, especially psychiatric patients. This study aims to determine the mental health services usage of outpatient psychiatric patients who attended a public mental health clinic in Tehran, during the quarantine. The study sample consisted of 387 patients with an active record in the mental health clinic. They were selected using systematic random sampling. Data was gathered with the telephone interviews using the researcher-made checklist. The data were then collected and analyzed. Results Participants in this study included 141 male and 264 female patients. One-hundred forty-two patients (36.7%) felt better during this period, and the rest got worse or did not make a difference. Among the patients who felt the need to visit, 144 (47.2%) referred for services, of which 81.7% had visited in person. Among the applicants, 84 (56%) succeeded in receiving the service. A total of 53.5% of patients had used at least one face to face, telephone, or online visit. Among them, women are compared to men (p = 0.002), educated people to low education (p < 0.001), and adults to children and the elderly (p = 0.02), and Tehran residents to foreigners (p = 0.01) used significantly more services. Conclusions Experience with pandemic quarantine conditions has shown that face-to-face use of these services faces significant barriers. In this situation, the expansion of online services can help improve the condition of patients and should be on the agenda of mental health policymakers.